Analisis Penerapan Penggunaan Media Pembelajaran Eksperimen Virtual dalam Pembelajaran IPA Kelas V SDN Sokosari 1 - Eri Latri Cahyani; Umul Latifah; Nurul Mahruzah Yulia (Yayasan Mutiara Hati Moeslem, 2026)
Science learning in elementary schools requires instructional media that can help students understand abstract concepts through more concrete learning experiences. However, limited laboratory facilities often hinder the implementation of direct experiments. This study aimed to analyze the implementation of virtual experiment learning media in fifth-grade science learning at SDN Sokosari 1. The study employed a descriptive qualitative approach involving a teacher and fifth-grade students as research subjects. Data were collected through interviews, observations, and documentation and analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that virtual experiment media were implemented in magnetism topics through simulations of magnetic fields, magnetic pole interactions, and electromagnets. The use of this media increased student engagement, facilitated understanding of abstract concepts, and created a more meaningful and interactive learning environment. Furthermore, digital media such as virtual simulations, YouTube, and Kahoot enhanced students’ learning motivation. Nevertheless, several challenges were identified, including limited instructional time and varying levels of student participation. Therefore, virtual experiment learning media can serve as an effective alternative to support science learning in elementary schools.